2001
DOI: 10.3346/jkms.2001.16.s.s19
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study on Cancer Prevention by Ginseng: Are All Kinds of Cancers Preventable by Ginseng?

Abstract: In the light of experimental results, two case-control studies and one cohort study in a population of ginseng cultivation area were conducted to confirm whether ginseng has any anticarcinogenic effect on human cancers. All participants were interviewed using a standardised questionnaire to obtain the information on demographics, cigarette smoking, alcohol consumption and ginseng intake. In 905 pairs case-control study, 62% had a history of ginseng intake compared to 75% of the controls, a statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 25 publications
1
46
0
1
Order By: Relevance
“…Hamed Jafari Vayghan 1 , Sevda Saleh Ghadimi 1 , Ali Reza Nourazarian 2,3 * (Yue et al, 2006) 4-reduce inflammatory responses, (Oh GS et al, 2004;Kimura et al, 2006) According to previous studies ginseng can be beneficial in the treatment and prevention of colorectal cancer (Yun and Choi 1995;Yun et al, 2001;Yun 2003a). The aim of this study was to review relevant literature on ginseng effects on colorectal cancer.…”
Section: Preventive and Therapeutic Roles Of Ginseng -Focus On Colon mentioning
confidence: 99%
See 1 more Smart Citation
“…Hamed Jafari Vayghan 1 , Sevda Saleh Ghadimi 1 , Ali Reza Nourazarian 2,3 * (Yue et al, 2006) 4-reduce inflammatory responses, (Oh GS et al, 2004;Kimura et al, 2006) According to previous studies ginseng can be beneficial in the treatment and prevention of colorectal cancer (Yun and Choi 1995;Yun et al, 2001;Yun 2003a). The aim of this study was to review relevant literature on ginseng effects on colorectal cancer.…”
Section: Preventive and Therapeutic Roles Of Ginseng -Focus On Colon mentioning
confidence: 99%
“…The anti-cancer effect of steamed ginseng was enhanced by antioxidants or inhibitors of the NF-κB pathway Previous studies have shown that Panax ginseng has anticancer activity (Shin et al, 2000;Shibata, 2001;Wang and Yuan 2008;Kim and Lee, 2010). An epidemiological study on 1000 subjects in Korea showed reduced the risk of a number of cancers including colorectal cancer in those taken Asian ginseng compared with those who did not use it (Yun and Choi 1995;Yun, Choi, and Yun 2001). Studies on ginsenosides especially Rg3 and Rh2 showed that they are most effective anti-cancer compounds identified in ginseng (Kim et al, 2004;Helms 2004;Li et al, 2009;Liu et al, 2009;).…”
Section: Effect Of Ginseng On Colorectal Cancermentioning
confidence: 99%
“…A major weakness of the data is that high-quality, rigorously controlled trials are lacking. Reasonable epidemiologic evidence suggests that Panax ginseng is a non-organ-specific cancer preventive, with a dose-response relationship 179 . Ginseng extracts and synthetic derivatives should be examined for their preventive effect on various types of human cancers.…”
Section: Prevention Of Cancer Progressionmentioning
confidence: 99%
“…Meyer has been associated with a decreased incidence of cancers that lack organ specificity, as well as cancers of the lung, stomach, liver, colorectum, and pancreas (5,6). Panax ginseng ingredients with anticarcinogenic and antimutagenic activities were identified as minor components in red ginseng (steamed and air-dried Panax ginseng) including ginsenosides Rg3, Rg5 and Rh2 (7,8).…”
Section: Introductionmentioning
confidence: 99%